2017
DOI: 10.1016/j.bbamem.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extracellular vesicles by IR spectroscopy: Fast and simple classification based on amide and C H stretching vibrations

Abstract: Extracellular vesicles isolated by differential centrifugation from Jurkat T-cell line were investigated by attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR). Amide and C-H stretching band intensity ratios calculated from IR bands, characteristic of protein and lipid components, proved to be distinctive for the different extracellular vesicle subpopulations. This proposed 'spectroscopic protein-to-lipid ratio', combined with the outlined spectrum-analysis protocol is valid also for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 46 publications
6
137
0
2
Order By: Relevance
“…Recently, Attenuated total reflection Fourier-transform Infrared Spectroscopy (ATR-FTIR) have been reported for simultaneous determination of protein and lipids from extracellular vesicles, without the need for extensive sample processing 28 . The distinctive absorption bands of proteins and lipid in the FTIR spectrum will www.nature.com/scientificreports www.nature.com/scientificreports/ also aid in the evaluation of Protein to Lipid (P/L) ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Attenuated total reflection Fourier-transform Infrared Spectroscopy (ATR-FTIR) have been reported for simultaneous determination of protein and lipids from extracellular vesicles, without the need for extensive sample processing 28 . The distinctive absorption bands of proteins and lipid in the FTIR spectrum will www.nature.com/scientificreports www.nature.com/scientificreports/ also aid in the evaluation of Protein to Lipid (P/L) ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Bruker Tensor-II series FTIR spectrometer. For protein to lipid ratio calculation, we adopted the methodology described earlier by Mihaly et al 28 10 µl of sample was mounted on the diamond ATR crystal and waited for ~45 minutes to form the thin dry film. The measurements were performed in ambient condition, immediately after thin film formation.…”
Section: Spectral Evaluation Of Enps By Ftir Atr-ftir Analysis Was Cmentioning
confidence: 99%
“…Quantification of total lipids can be achieved, e.g. by sulfophosphovanilin assay [186], by measuring fluorescence of phospholipid dyes that fluoresce only when incorporated into lipid bilayers, such as DiR [187], or by total reflection Fourier-transform infrared spectroscopy [188]. However, the latter requires specialized equipment, and the former two types of assays may be insufficiently sensitive for small amount of EVs.…”
Section: ) Intermediate Recovery Intermediate Specificity: Methods mentioning
confidence: 99%
“…Importantly, ratios of the different quantification methods may provide useful measures of purity. For example, protein:particle ratio [198,199], protein: lipid ratio [186,188,200] and RNA:particle [201] have been proposed as possible purity metrics, although their applicability across protein, lipid, RNA and particle quantification methods remains to be established. Techniques that measure multiple parameters at once, such as colloidal nanoplasmonic assays or infrared (IR) spectroscopy [188,199] may be good optional methods, despite the need for specific sensors or other equipment.…”
Section: ) Intermediate Recovery Intermediate Specificity: Methods mentioning
confidence: 99%
“…Consequently, additional techniques that could rapidly provide further structural information on these systems are highly desirable . In this respect, we recently demonstrated that attenuated total reflection Fourier‐transform infrared (ATR‐FTIR) spectroscopy is a fast and reliable method that can provide insight into compositional changes of EV subpopulations without complicated sample preparations . To progress further towards rapid investigation of EVs at the molecular level, here we employed polarized light spectroscopy techniques, namely, linear dichroism (LD) and also circular dichroism (CD), that are commonly applied for model membrane systems, but their use in EV research is scarce.…”
Section: Figurementioning
confidence: 99%